Yeast cell fate control by temporal redundancy modulation of transcription factor paralogs - Yan Wu (Nature Portfolio, 2021)
How dynamic transcription factors temporally interact to regulate stress survival in yeast is currently unclear. Here the authors integrate single-cell imaging, RNA-seq, and modeling to identify a new cell fate control mechanism mediated by temporal redundancy modulation during yeast stress response.